The effect of temperature and strain rate on the grain boundary sliding in a CM247 LC Ni-based superalloy processed with laser based powder bed fusion - P.A. Martelli; I. Sabirov; M.A. Monclus; E. Bassini; G. Marchese; D. Ugues (Journal of Materials Research and Technology, 2024)
The current work explores the meso-scale deformation behaviour of an additively manufactured CM247 LC at room and high temperatures. In particular, the study focuses on assessing grain boundary sliding (GBS), which can play a crucial role in the high-temperature deformation of superalloys. Specific samples were produced using the Laser Based Powder Bed Fusion technique (PBF-LB), heat treated and tested under monotonic compression in a Gleeble® system. Compression tests were carried out in a wide temperature range at two strain rates and the effect of testing parameters on GBS activity was studied. A thorough microstructural characterization of the PBF-LB material using EBSD and TEM revealed a γ/γ’ microstructure consisting of columnar grains decorated with Hf-rich MC carbides without any segregations of alloying elements. Qualitative and quantitative analysis of GBS was performed using FEG-SEM and AFM, and contribution of GBS into plastic deformation was estimated. It was demonstrated that GBS is activated at 760 °C. A direct correlation between the contribution of GBS into plastic deformation and testing temperature was found, while strain rate has the opposite effect. The highest GBS contribution (∼32%) was recorded at 1093 °C/10−3 s−1. Finally, intergranular microcracking at triple junctions and along grain boundaries was observed when the material was tested at the highest temperatures (871 °C and 1093 °C). The effect of the temperature and the strain rate on the GBS activity in the PBF-LB material is discussed.